2005
DOI: 10.1111/j.1478-4408.2005.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching of indigo‐dyed denim fabric by electrochemical formation of hypohalogenites in situ

Abstract: The use of hypochlorite, formed in situ by anodic oxidation of sodium chloride solution, for bleaching indigo‐dyed denim has been studied at room temperature and at 50 °C. A direct relationship between the charge flow applied and the bleaching effect was observed. This enables consistent oxidative bleaching to be achieved by controlling the electrochemical process. The use of mixed anolytes containing small concentrations of bromide ions enhanced the bleaching effect considerably, even after lowering the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The colours are described in CIELab-coordinates, L corresponding to the brightness (100 = white, 0 = black), a to the redgreen coordinate (positive sign = red, negative sign = green) and b to the yellow-blue coordinate (positive sign = yellow, negative sign = blue). Details for the bleach effect are given elsewhere [11,20].…”
Section: Technical Scale Processmentioning
confidence: 99%
See 4 more Smart Citations
“…The colours are described in CIELab-coordinates, L corresponding to the brightness (100 = white, 0 = black), a to the redgreen coordinate (positive sign = red, negative sign = green) and b to the yellow-blue coordinate (positive sign = yellow, negative sign = blue). Details for the bleach effect are given elsewhere [11,20].…”
Section: Technical Scale Processmentioning
confidence: 99%
“…Details describing bleach effects and comparison of bleach results are given elsewhere [11,20]. The comparison of the bleach effects indicated that, under similar process conditions e.g.…”
Section: Bleach Processmentioning
confidence: 99%
See 3 more Smart Citations